Tissue-specific variations of esterase activities in the tadpoles and adults of Pseudis paradoxa (anura: Hylidae) - Attademo, Andres Maximiliano (2014)
We determined basal levels of cholinesterase (ChE) and carboxylesterase (CbEs; two substrates: α- naphthyl acetate and 4-nitrophenylvalerate) in different tissues of tadpoles and adults of the frog Pseudis paradoxa and evaluated their use as complementary biomarkers of anti-cholinesterase pesticide exposure. ChE and CbEs sensitivity to malaoxon was also evaluated. Adults and tadpoles were collected with sweep net from temporary ponds located in natural riparian forests along the Paraná River (Garay Department, Santa Fe province, Argentina). We found significant differences in B-esterase activities between adults and tadpoles and among different tissues. The in vitro inhibition tests indicated that ChE is more sensitive to inhibition than CbEs. Our results suggest that basal ChE and CbE (α-NA and 4- NPV) activities in different tissues of adult and tadpoles P. paradoxa would be suitable biomarkers of pesticide exposure, and this amphibian species could be used as sentinel in field monitoring.